Autophagy as a Survival Strategy for Eukaryotic Microbes Living in the Phyllosphere - Shiraishi, Kosuke; Sakai, Yasuyoshi (Frontiers in Plant Science, 2022)
Autophagy is an intracellular degradation process that is highly conserved among eukaryotes at the molecular level. The process was originally revealed in the budding yeast, but the physiological role of autophagy in yeast cells had remained unknown as autophagy-deficient yeast mutants did now show a clear growth phenotype in laboratory conditions. In this review, we introduce the role of autophagy in the methylotrophic yeast Candida boidinii grown on the leaf surface of Arabidopsis thaliana. Autophagy is shown to be required for proliferation in the phyllosphere, and selective autophagic pathways such as pexophagy and cytoplasm-to-vacuole targeting (Cvt) pathway are strictly regulated during both the daily cycle and the host plant life cycle. This review describes our current understanding of the role of autophagy as a survival strategy for phyllosphere fungi. Critical functions of autophagy for pathogen invasions are also discussed.